Denegatio iuris in the context of esclusion of marriage fidelity - LESZCZYŃSKI, GRZEGORZ (Prawo Kanoniczne, 2019)
Taking up the value of marriage consens and its esclusion in the context of declaring a marriage null and voit, the author begins his reflections with a look at one of the marriage property that is marriage unity and fidelity. From the point of view of marriage validity, of special significance is also the analysis of esclusion of fidelity in the practice exsamples. The last part of the author’s reflections is devoted to the analysis of distinction between simple infedility and esclusion of right to esclusivity and fidelity in the context of marriage.